FIELD WET CAPACITY IN THE SOIL (Spectrum Journal of Innovation, Reforms and Development, 2024)
At every point in the world, there are unique climatic conditions and glabal water problems. Due to changes in the contingent climate, there is a shortage of available resources, educational conditions, and various waterfalls. (Matthew 24:14; 28:19, 20) Therefore, the use of transparency technologies to irrigate agricultural crops is one of the most complex problems of our day. Before irrigation, the CHDNS of the field plays a vital role in its economic development, avoiding excessive costs that add to the properties. On time, the need to irrigate crops in its own way is indicated by the wet capacity of a field.